Determinação do perfil químico e atividade biológica do extrato etanólico de curcuma longa linn e avaliação do uso em uma formulação para o tratamento de dermatites - Pinheiro, Marcos André de Paula (2024)
Curcuma longa Linn is a plant species that various civilizations and people over the years have used as a healing agent against the most diverse illnesses. Curcumin and other curcuminoids found in the studied species are antioxidant and anti-inflammatory compounds that are promising for use in pharmaceutical forms and can be used to treat dermatitis. The work aimed to propose a formulation containing ethanolic extract of C. longa that can be used in the treatment of dermatitis. The chemical characterization of the extract was carried out using classical phytochemical tests, spectrophotometric analysis and instrumental analysis such as high performance liquid chromatography and mass spectrometry. To evaluate the biological activity, the in vitro antioxidant action against the DPPH radical was determined. A hydroalcoholic gel was proposed with the introduction of the alcoholic C. longa extract and its stability under different packaging conditions was determined, as well as its permeation in an ex vivo model using porcine tissue to mimic skin permeation. From the LC/(-)ESI-Q-TOF MS analysis, it was possible to identify curcumin and other curcuminoid markers, alongside phenolic compounds and terpenes. Using spectrophotometric techniques, it was possible to determine the total phenolic compound content of 988.36 ± 3.75 mg EAG/g of extract, and the flavonoid content of 43.62 ± 1.12 mg ER/g of extract. Through HPLC analysis, the curcumin content was determined to be 437.73 ± 1.11 mg/g of extract. The extract showed DPPH radical reduction activity and an IC50 = 24.49 ± 1.69 µg/mL. And through stability studies, it can be proven that when stored under refrigeration and protected from light, a gel with C. longa extract has its degradation delayed, when compared to other storage conditions. The permeation test showed that the gel with C. longa extract obtained greater curcumin permeation than a standard solubilized in a permeation promoter. The chemical diversity of the ethanolic extract of C. longa was explored, as well as the quantification of the main marker, curcumin, resulting in the production of a formulation with antioxidant activity, which obtained promising permeation results.